Case report: Diversity of imaging in cardiac angiosarcoma: two cases with disparate enhancement and metabolic manifestations - Chen, Sinan; Cen, Huan; Zhao, Jie; Ran, Pengcheng; Lu, Weihui; Sun, Pengtao (Frontiers in Oncology, 2025)
Cardiac angiosarcoma, a rare and aggressive malignancy arising from endothelial cells, is difficult to diagnose owing to its nonspecific clinical symptoms and variable imaging features. Two cases of cardiac angiosarcoma (CA) are presented, each with different enhancement and metabolic patterns on imaging. Case 1: A 59-year-old man presented with chest tightness and lower extremity edema. Ultrasound and computed tomography (CT) imaging revealed a hypoechoic/hypodense, non-enhancing mass with pericardial thickening in the right atrium. Positron emission tomography (PET) showed minimal uptake and, given that the patient had elevated D-dimer and fibrinogen levels, a thrombus was initially suspected. However, surgical intervention ultimately led to a diagnosis of CA. Case 2: A 27-year-old man presented with dyspnea and cough. Both ultrasound and CT imaging revealed a mass in the right atrium, with mid-to-low echogenic/hypodense features, heterogeneous enhancement, and pericardial effusion, along with pericardial thickening. A PET scan showed a significant increase in radiotracer uptake within the mass, strongly suggestive of CA. Surgical intervention subsequently confirmed the diagnosis of CA. These two cases demonstrate the presence of distinct enhancement and metabolic patterns on imaging in primary CA and indicate the importance of considering a wide range of enhancement features and metabolic activities in the differential diagnosis of patients presenting with non-specific cardiac symptoms.